PSYCHOLOGICAL EXPECTATIONS AND TURNOVER INTENTION AMONG AIRLINE EMPLOYEES: THE MEDIATING ROLES OF PERCEIVED VALUE AND SENSE OF ACHIEVEMENT - Yanru, Deng (МІЖНАРОДНА ЕКОНОМІКА В УМОВАХ КЛІМАТИЧНИХ ЗМІН: ГЛОБАЛЬНІ ВИКЛИКИ, 2026)
.